2020
DOI: 10.1111/jssr.12700
|View full text |Cite
|
Sign up to set email alerts
|

Does Religious Affiliation Protect People's Well‐Being? Evidence from the Great Recession after Correcting for Selection Effects

Abstract: This paper investigates the effect of religious affiliation on individual well‐being. Using Gallup's U.S. Daily Poll between 2008 and 2017, we find that those who are engaged in their local church and view their faith as important to their lives have not only higher levels of subjective well‐being, but also acyclical levels. We show that the acyclicality of subjective well‐being among Christians is not driven by selection effects or the presence of greater social capital, but rather a sense of purpose over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 90 publications
0
7
0
1
Order By: Relevance
“…Lindström and Giordano [64] find that after the 2008 economic crisis social capital and trust became an important buffer against poor psychological wellbeing. Moreover, using data between 2008 and 2017, Makridis et al [65] show that religiosity also mediates the effects of business cycle fluctuations on individual well-being. While the average individual exhibits significant cyclicality in their reported life satisfaction, active Christians not only exhibit higher levels of life satisfaction, but also acyclical levels.…”
Section: Social Capital and Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Lindström and Giordano [64] find that after the 2008 economic crisis social capital and trust became an important buffer against poor psychological wellbeing. Moreover, using data between 2008 and 2017, Makridis et al [65] show that religiosity also mediates the effects of business cycle fluctuations on individual well-being. While the average individual exhibits significant cyclicality in their reported life satisfaction, active Christians not only exhibit higher levels of life satisfaction, but also acyclical levels.…”
Section: Social Capital and Covid-19mentioning
confidence: 99%
“…These indicators, at the county-level, include: the share of births in the past year to women who were unmarried, the share of women ages 35-44 who are currently married and not separated, the share of own children living in a single-parent family, registered non-religious non-profits per 1,000, religious congregations per 1,000, an informal civil society sub-index, and the average of votes in the Presidential election per citizen ages 18 and over. The civil society sub-index includes: combination of share who volunteered, who attended a public meeting, who report having worked with neighbors to fix/ improve something, who served on a committee or as an officer, who attended a meeting where politics was discussed, and who took part in a demonstration in the past year [see also 65]. These data are generally compiled based off of estimates from 2012 to 2016-well before COVID-19 and, therefore, predetermined with respect to current infection rates and the spread of the virus.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Upenieks, Schieman, and Bierman (2022) found that a sense of divine control was associated with better mental health outcomes when confronting the Great Recession in the United States. This was attributed to individuals actively seeking out religious doctrine “in response to a stressor and its impact on mental health” to “draw closer to God.” Makridis, Johnson, and Koenig (2021) found similar advantages in facing the Great Recession in terms of religious identification, religiosity, and having a sense of divine purpose. After Hurricane Katrina, positive religious coping was associated with mental health benefits and other indicators of well‐being, while negative coping or religious strain was associated with deleterious mental health outcomes (Cook et al.…”
Section: Theory and Hypothesementioning
confidence: 93%
“…Religion provides repertoires for managing emotional suffering and coping with uncertainty and adversity (Pargament 2001). Decades of research reveal a consistent pattern whereby people turn to religion and find resources for coping when facing unprecedented disastrous events (Bentzen 2019;Cook et al 2013;Henslee et al 2015;Makridis, Johnson, and Koenig 2021;Schuster et al 2001). Said otherwise, people turn to religion as a resource for coping.…”
Section: Introductionmentioning
confidence: 99%